2019
DOI: 10.1002/1348-9585.12020
|View full text |Cite
|
Sign up to set email alerts
|

Social support at work and mental distress: A three-wave study of normal, reversed, and reciprocal relationships

Abstract: Objectives This longitudinal study aimed to investigate the causal relationships between social support at work and mental health in terms of mental distress. Despite assuming social support at work to be associated with less mental distress, reversed and reciprocal relationships were investigated as well. Methods Self‐reports in questionnaires of social support and mental distress were collected longitudinally, with annual measurements over three consecutive years, amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
(153 reference statements)
0
7
1
2
Order By: Relevance
“…By contrast, we examined these pathways in a heterogeneous sample of the general working population in Canada. Differences between studies in the underlying prevalence and distribution of relevant measures could explain the observed discrepancy between our findings and those reported using samples of workers employed in specific occupations 78 . Finally, and perhaps most significantly, previous research in this area has by and large focused on a relatively narrow set of work exposures—namely, on the most common measures of job demands (eg, quantitative workload and time pressure) 45 .…”
Section: Discussioncontrasting
confidence: 74%
“…By contrast, we examined these pathways in a heterogeneous sample of the general working population in Canada. Differences between studies in the underlying prevalence and distribution of relevant measures could explain the observed discrepancy between our findings and those reported using samples of workers employed in specific occupations 78 . Finally, and perhaps most significantly, previous research in this area has by and large focused on a relatively narrow set of work exposures—namely, on the most common measures of job demands (eg, quantitative workload and time pressure) 45 .…”
Section: Discussioncontrasting
confidence: 74%
“…Beide blokken zijn aangepaste versies van soortgelijke vragen uit de NEA. Een positief, ondersteunend sociaal klimaat is van belang voor het welzijn van medewerkers (Sconfienza et al, 2019). Daarnaast is er, alleen voor medewerkers in een zorginstelling, een derde vragenblok over het omgaan met cliënten.…”
Section: Middellange Termijn: Vitaliteitunclassified
“…Numerous studies have shown that social support can effectively improve students' learning outcomes and enhance their learning retention (Goggins & Xing, 2016; Hsu et al, 2018; Sconfienza et al, 2019). This study contributes by proposing SafeMathBot to enhance its generation safety without sacrificing its capability to provide social support.…”
Section: Discussionmentioning
confidence: 99%
“…Social support theory enables researchers to examine how students share learning resources, assuming that the resource provider or receiver would benefit from the exchange (Shumaker & Brownell, 1984). Studies have found that students' learning gains (Goggins & Xing, 2016), relationship reciprocity and sustainability (Sconfienza et al, 2019), and learning engagement (Hsu et al, 2018) were positively associated with social support. Researchers often examined social support from three dimensions: informational, emotional and community support.…”
Section: Dimensions Of Support Through the Lens Of Social Support Theorymentioning
confidence: 99%